Characterization of Dolomite Stone Broken Under Axial Impact - Ran Ji; Han Chen; Huaizhong Shi; Wenhao He; Dong Liu; Yongqi Wang (Applied Sciences)
As the extraction of oil and gas progresses into deeper and ultra-deep geological formations, the enhancement of rock-breaking efficiency in drill bits has emerged as a critical factor in ensuring energy security. Among the various techniques employed, vibratory percussion drilling technology is widely recognized for its ability to improve both the efficiency and speed of penetrating hard rock formations. This study examined the effects of varying loading conditions on the characteristics of rock fracture and damage, maintaining a constant cutting speed and lead angle. By designing a small polycrystalline diamond compact (PDC) drill bit and incorporating simulation results, the research sought to analyze the influence of axial impact components on the efficiency of breaking dolomite samples, as well as the effects of impact frequency and amplitude on drilling pressure and rock-breaking energy. The findings revealed that an increase in the axial impact amplitude significantly enhanced rock-breaking efficiency, elevated von Mises stress, and increased principal compressive stress. An increase in impact frequency effectively reduced the overall stress and frictional work. These results underscored that the stress analysis revealed that the peak stress increased at lower impact amplitudes, with notable changes occurring at an amplitude of 1.5, leading to a 100% increase in Mises peak stress compared with an amplitude of 1.0. Axial impact drilling promoted deep crack formation and the development of a tensile damage zone beneath the cutter, indicating its effective rock-breaking capabilities. Axial impact drilling significantly reduced the threshold drilling pressure compared with conventional rotation, with an impact amplitude of 0.3 mm decreasing the static load by 44.1%. Additionally, increasing the axial impact amplitude enhanced the rate of penetration (ROP) while maintaining a constant static load, resulting in remarkable efficiency improvements. The results of the study are expected to provide theoretical guidance for the mechanism of impact rock breaking and the design of impact rock-breaking tool parameters.